Following the Wrong Rules? : A Linguistic Study of Novice Academic Writing - Jungwirth, Robin; Woznicki, Nathaniel; Schermer, Sky; Gillis, Mary; Wolter, Lynsey K. (My University, 2017)
Corpus linguistics makes use of large collections of texts to scientifically study the language used in texts and speech. Using corpus linguistics we are exploring the difference between novice and professional academic writers.
Color poster with text, graphs, and models.
Keywords: Academic writing; Corpus linguistics; Linguistics; Posters